A new workerless inquiline in the Lower Attini (Hymenoptera: Formicidae), with a discussion of social parasitism in fungus-growing ants - Rabeling, Christian; Bacci Junior, Mauricio [UNESP] (Wiley-Blackwell, 2010)
Ant inquilines are obligate social parasites, usually lacking a sterile worker caste, which are dependent on their hosts for survival and reproduction. Social parasites are rare among the fungus-gardening ants (Myrmicinae: tribe Attini) and only four species are known until now, all being inquilines from the Higher Attini. We describe Mycocepurus castrator sp.n., the first inquiline social parasite to be discovered in the Lower Attini. Our study of the parasite's behaviour and life history supports the conclusion drawn from external morphology: Mycocepurus castrator is an evolutionarily derived inquiline parasite of Mycocepurus goeldii. Inquilines are of great interest to evolutionary biology because it is debated if they originated via sympatric or allopatric speciation. We discuss the life history evolution, behaviour and morphology of socially parasitic, fungus-growing ants.